Pengaruh Pengungkapan Emisi Karbon dan Kinerja Lingkungan terhadap Nilai Perusahaan dengan Biaya Lingkungan sebagai Variabel Moderasi - Bunga Syalaisha Putri (AKUNTANSI 45, 2026)
This study analyzes carbon emissions disclosure, environmental performance, environmental costs, and their impact on the company value of PT Adaro Energy Indonesia Tbk during the period of 2018-2022. The results show that PT Adaro Energy consistently discloses carbon emissions with a disclosure score of 1 each year, reflecting the company's commitment to transparency and environmental regulations. The company’s environmental performance also improved, as evidenced by achieving the PROPER KLHK Gold rating for four consecutive years (2019-2022). However, the company’s value, measured using the Price Book Value ratio, declined from 1,325 in 2018 to 598 in 2022, despite improvements in environmental performance. Environmental costs showed significant fluctuations, with a sharp increase in 2022, indicating substantial investment in environmental initiatives. This study suggests that PT Adaro Energy enhance communication with investors regarding the long-term benefits of sustainability, continue innovating in eco-friendly technologies, and expand its CSR programs. Periodic evaluations of environmental costs are also necessary to improve the efficiency and effectiveness of environmental investments in supporting the company’s sustainability.